2013
DOI: 10.1590/s1517-83822013005000025
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of Nisin, Pediocin 34 and Enterocin FH99 against Listeria monocytogenes and cross resistance of its bacteriocin resistant variants to common food preservatives

Abstract: Antilisterial efficiency of three bacteriocins, viz, Nisin, Pediocin 34 and Enterocin FH99 was tested individually and in combination against Listeria mononcytogenes ATCC 53135. A greater antibacterial effect was observed when the bacteriocins were combined in pairs, indicating that the use of more than one LAB bacteriocin in combination have a higher antibacterial action than when used individually. Variants of Listeria monocytogenes ATCC 53135 resistant to Nisin, Pediocin 34 and Enterocin FH99 were developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 48 publications
5
36
0
2
Order By: Relevance
“…The bactericidal activity against this pathogen resulting from this combination was higher than that of either bacteriocin alone. Similar results were observed by Kaur et al (2013), who combined nisin, pediocin 34 and enterocin FH99 (both suclass IIa bacteriocins) to control L. monocytogenes. Moreover, the combination of nisin (500 IU ml 21 ) and pediocin PA-1 (1720 AU ml 21 ) reduced the frequency of resistance development (a 10 2 -10 4 reduction, depending on the strain tested) in L. monocytogenes (Gravesen et al, 2002a).…”
Section: Strategies To Overcome Bacteriocin Resistancesupporting
confidence: 80%
See 1 more Smart Citation
“…The bactericidal activity against this pathogen resulting from this combination was higher than that of either bacteriocin alone. Similar results were observed by Kaur et al (2013), who combined nisin, pediocin 34 and enterocin FH99 (both suclass IIa bacteriocins) to control L. monocytogenes. Moreover, the combination of nisin (500 IU ml 21 ) and pediocin PA-1 (1720 AU ml 21 ) reduced the frequency of resistance development (a 10 2 -10 4 reduction, depending on the strain tested) in L. monocytogenes (Gravesen et al, 2002a).…”
Section: Strategies To Overcome Bacteriocin Resistancesupporting
confidence: 80%
“…Kaur et al (2013) showed that L. monocytogenes mutants resistant to nisin, pediocin 34 and enterocin FH99 did not become resistant to low pH, sodium chloride, potassium sorbate or sodium nitrite. Resistant variants were equally or more sensitive than the WT strain.…”
Section: Strategies To Overcome Bacteriocin Resistancementioning
confidence: 99%
“…Some examples of antimicrobials which have been proven to be active against L. monocytogenes include lauric arginate, chitosan, pediocin, and nisin (Kaur et al, 2013; Kang et al, 2015). Nisin is one of the most common antimicrobials used in the food industry especially within dairy products and acidic foods (Delves-Broughton et al, 1996).…”
Section: Stresses Encountered In Foodmentioning
confidence: 99%
“…Recently, Sant'Anna et al [31] demonstrated that the peptide P34 showed potential to control . However, increasing tolerance or resistance of L. monocytogenes strains to nisin has been reported [26], indicating the importance of research on new substances showing antilisterial activity [27][28][29].…”
Section: Inhibition Of L Monocytogenes In Minas Cheesementioning
confidence: 99%